Peer Interaction During Grammar Tasks: How Do Learners Assist Each Other? - Fujita, Yasuko (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2001)
This paper presents an analysis of assisted performance in pattern drills, where learners practice grammar patterns of Japanese as a foreign language at a university. Results reveal that the method of assistance employed by learners varies with the task in which they are engaged, regardless of the goal of the task. In the conjugation drill, learners used methods of co-construction, next turn repair initiation (NTRI) with repair, and waiting to assist peers. Access to the answers makes it easier for learners to assist other learners when they have difficulty. In the pseudo Question and Answer (QA) drill, learners employed methods of NTRI with repair and waiting, which implies that learners are able to engage themselves in a task without assistance. Learners’ behavior toward these drills can differ. The analysis of two tasks shows that learners use different methods of assisted performance, not only in the configuration of the task but also in the nature of the task in learning grammar features of a second/foreign language (L2).